The Quality of Internal Auditing and Its Role in Rationalising Financial Decisions : (A Field Study on A Sample of Banks in Sudan) - د. ياسر تاج السر محمد سند; إسراء معاوية إسماعيل ميرغني (White Nile Journal for Studies and Research, 2026)
The study aimed to test the role of internal audit quality in rationalising financial decisions (investment and financing) in banks in Sudan. The problem addressed in the study was the low efficiency of these decisions, as reflected in the credit crisis and liquidity crisis suffered by the banking sector, with negative indicators such as an increase in non-performing loans and a decline in return on investment. The study adopted a descriptive analytical approach. The results showed a statistically significant positive relationship between the quality of internal auditing and both the rationalisation of investment decisions (through investment analysis and risk assessment) and the rationalisation of financing decisions (through the provision of accurate and reliable reports). The study recommends supporting the internal audit function with advanced risk analysis mechanisms and strengthening its systems to provide high-quality data, thereby contributing to improved financial decision-making. Keywords: Internal Audit Quality. Financial Decisions, Investment Decisions, Financing Decisions